Durable Response to Treatment With Combination Radiotherapy and High-dose Interleukin-2 in Metastatic Chromophobe Variant Renal Cell Carcinoma. Issue 2 (February 2016) - Merriman, Joseph; Tward, Jonathan; Albertson, Dan; Dechet, Christopher; Agarwal, Neeraj
Abstract : This is a report of chromophobe renal cell carcinoma (ChRCC), a rare entity that accounts for 6% to 11% of cases of renal cell carcinoma (RCC). ChRCC is considered to yield a good prognosis as it typically presents as an early stage tumor with longer overall survival when compared with clear cell RCC; however, metastatic disease negates this survival difference and is characterized by poor prognosis. The available clinical investigations supporting the guidelines for treatment of metastatic RCC are predominantly based on clear cell RCC studies. There are no data supporting the applicability of guidelines used to treat clear cell to the management of patients with the ChRCC. This case report describes a male patient who initially presented with locally advanced chromophobe variant RCC, pathologically staged T3aN1M0, initially treated with radical nephrectomy. After developing pathologically confirmed metastatic disease, the patient was treated with repeated cycles of combined hypofractionated radiotherapy to symptomatic metastatic disease sites followed by high-dose intravenous interleukin-2 (HD IL-2) subsequently achieving a near complete and durable response. Three months after initiation of HD IL-2 and radiotherapy, the patient achieved a partial response, and after 6 months he achieved a near complete response. At the time of most recent follow-up, over 36 months after the diagnosis of metastatic disease, the patient remained in remission. On the basis of this experience, we hypothesize that immunomodulation from the radiation potentiated an immune response to HD IL-2 leading to near complete and a durable response in this patient with metastatic ChRCC.